2019
DOI: 10.1021/acsami.9b00908
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Template-Free Fabrication of Ultrathin Mixed-Valence Polyoxovanadate-Incorporated Metal–Organic Framework Nanosheets for Highly Efficient Selective Oxidation Catalysis in Air

Abstract: Polyoxometalate (POM)-based metal–organic frameworks (MOFs) with nanostructure represent a class of promising heterogeneous nanocatalysts. As yet, direct one-step controllable synthesis of pure nanoscale POM-MOFs catalysts is an extremely huge challenge owing to highly complicated synthetic conditions. Herein, for the first time, we fabricated ultrathin (∼5 nm) mixed-valence {V16} clusters-incorporated metal–organic framework nanosheets [Ni­(4,4′-bpy)2]2 [V7 IVV9 VO38Cl]·(4,4′-bpy)·6H2O (NENU-MV-1a) via one-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 71 publications
0
31
0
Order By: Relevance
“…In 2008, six kind of Keggin-type POMs were encapsulated into Cu-BTC (named NENU-n, NENU = Northeast Normal University) using a one-pot hydrothermal method and their crystal structures were determined [43]. Subsequently, various POMs were encapsulated into the Cu-BTC framework and their catalytic performance was examined in ODS reactions [67,68], the oxidation of alcohols [69,70], olefins [39,[71][72][73], benzene, and H2S [41,74]. For example, Zheng et al prepared different sizes of nanocrystal-based catalysts, [Cu2(BTC)4/3(H2O)2]6[H5PV2Mo10O40] (NENU-9N), by using various copper salts and adjusting the pH of the solution for the ODS reaction (see Figure 3) [75].…”
Section: Oxidation Reactionmentioning
confidence: 99%
“…In 2008, six kind of Keggin-type POMs were encapsulated into Cu-BTC (named NENU-n, NENU = Northeast Normal University) using a one-pot hydrothermal method and their crystal structures were determined [43]. Subsequently, various POMs were encapsulated into the Cu-BTC framework and their catalytic performance was examined in ODS reactions [67,68], the oxidation of alcohols [69,70], olefins [39,[71][72][73], benzene, and H2S [41,74]. For example, Zheng et al prepared different sizes of nanocrystal-based catalysts, [Cu2(BTC)4/3(H2O)2]6[H5PV2Mo10O40] (NENU-9N), by using various copper salts and adjusting the pH of the solution for the ODS reaction (see Figure 3) [75].…”
Section: Oxidation Reactionmentioning
confidence: 99%
“…Research into catalytic process optimization covers catalyst development ranging from a selection of several transitions metals (mostly) and their ability to work under a selection of homogeneous or heterogeneous versions with a wide range of supporting materials available [11][12][13]. Beyond that, research also devotes effort to determining the most suitable oxygen source (ideally dioxygen, but also organic peroxides or hydrogen peroxide), physical conditions (pressure and temperature), and the solvent [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the reference samples Ag-trz 3 , CH 3 COOAg and PMA were obviously dissolved in the reaction mixture, revealing the homogeneous nature of these catalysts. By comparing with the related heterogeneous catalysts reported in literature work [31], we used less catalyst and isobutyraldehyde in the reaction, and also used a higher solvent dose. We therefore found that catalyst 1 has a much higher activity than the nickel-complex modified polyoxometalate catalyst in literature [31] for the epoxidation of cyclooctene with O 2 /IBA (Table 1).…”
Section: Catalytic Propertiesmentioning
confidence: 99%
“…After introducing the PMA into the infinite three-dimensional polycatenated framework, the Mo3d peaks shift slightly toward lower binding energies (Mo3d5/2 at 232.75 eV and Mo3d3/2 at 235.85 eV), further reflecting the presence of interaction between PMA units and the polycatenated framework. In general, the polycatenane compounds have a relatively large open framework, which is suitable for the diffusion of the reactants to increase the substrate contact with the catalyst active sites, thus helping to improve the catalytic activity [31,42,44]. Meanwhile, the formation of multidimensional supramolecular structure through multiple weak interactions, such as charge interaction and hydrogen bonds, should be very critical in fabricating highly efficient and stable POM-based catalysts [12,42,45].…”
Section: Catalytic Propertiesmentioning
confidence: 99%